2012
DOI: 10.15809/irriga.2012v1n01p408
|View full text |Cite
|
Sign up to set email alerts
|

Produção De Mudas De Timbaúba Sob Diferentes Concentrações De Efluente Doméstico Tratado

Abstract: A caatinga é um ecossistema frágil que sofre com as alterações causadas devido a exploração de espécies nativas modificando o seu ecossistema e causando problemas ambientais tais como a desertificação. O uso de água residuária na produção de mudas nativas é uma alternativa sustentável para recuperar ecossistemas degradados e preservar a água pura. Objetivou-se com este trabalho para produção de mudas de Timbaúba com o uso de água residuária tratada. Neste experimento foram usadas cinco diferentes dosagens de e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
4
0
5
Order By: Relevance
“…of DBS and the application of 190.7 mg dm -3 of N contributed positively only to the increase of shoot:root dry matter ratio. Nitrogen is one of the most important nutrients for plants, being the essential constituent of amino acids, proteins, nitrogenous bases, nucleic acids, hormones, and chlorophyll, among other molecules necessary for the growth and development of plants (Costa et al, 2012;. On the other hand, DBS is a substrate with high nutrient contents as previously reported by Amaral et al (2010), which showed that the DBS had a pH of 6.8, 0.31 mS cm -1 of electrical conductivity, 1.98 mg L -1 of nitrogen, 22.77 mg L -1 of potassium, 2.13 mg L -1 of calcium and 0.93 mg L -1 of magnesium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of DBS and the application of 190.7 mg dm -3 of N contributed positively only to the increase of shoot:root dry matter ratio. Nitrogen is one of the most important nutrients for plants, being the essential constituent of amino acids, proteins, nitrogenous bases, nucleic acids, hormones, and chlorophyll, among other molecules necessary for the growth and development of plants (Costa et al, 2012;. On the other hand, DBS is a substrate with high nutrient contents as previously reported by Amaral et al (2010), which showed that the DBS had a pH of 6.8, 0.31 mS cm -1 of electrical conductivity, 1.98 mg L -1 of nitrogen, 22.77 mg L -1 of potassium, 2.13 mg L -1 of calcium and 0.93 mg L -1 of magnesium.…”
Section: Resultsmentioning
confidence: 99%
“…During the seedling production phase of this species, some management factors must be considered, in order to increase the germination rate and to provide faster growth and uniformity of the cagaita plants (Souza et al, 2001). Among these factors, the proper management of fertilization, especially of nitrogen, should be highlighted, since this essential nutrient is directly related to some mechanisms and metabolic processes of the plant, such as photosynthesis, respiration, root development, nutrient absorption, differentiation cellular and growth (Costa et al, 2012). Another factor to be highlighted is the type of substrate used, since the substrate is responsible for nutrient supply, aeration, and water retention, providing conditions for the proper growth and development of the plant root system (Alves et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Distribui-se pelos estados do Pará, Maranhão e Piauí até o Mato Grosso do Sul e Rio Grande do Sul, como também, nas florestas pluviais e semidecíduas (COSTA et al, 2009). Sua madeira é considerada de durabilidade mediana, podendo ser empregada na fabricação de canoas, móveis, portas, caixotaria em geral e construção civil (LORENZI, 2002;COSTA et al, 2012).…”
Section: Introductionunclassified
“…The increase in the number of leaflets in K. ivorensis seedlings provided by two treatments is a favorable result regarding its application, since according to Costa et al (2012), leaves and leaflets contribute to a greater photosynthetic activity, supplying plants in terms of energy and contributing to their development.…”
Section: /7mentioning
confidence: 99%